Nanomedical engineering: shaping future nanomedicines. (6th November 2014) - Luo, Dandan; Carter, Kevin A.; Lovell, Jonathan F.
Abstract : Preclinical research in the field of nanomedicine continues to produce a steady stream of new nanoparticles with unique capabilities and complex properties. With improvements come promising treatments for diseases, with the ultimate goal of clinical translation and better patient outcomes compared with current standards of care. Here, we outline engineering considerations for nanomedicines, with respect to design criteria, targeting, and stimuli‐triggered drug release strategies. General properties, clinical relevance, and current research advances of various nanomedicines are discussed in light of how these will realize their potential and shape the future of the field. WIREs Nanomed Nanobiotechnol 2015, 7:169–188. doi: 10.1002/wnan.1315 This article is categorized under: Therapeutic Approaches and Drug Discovery > Emerging Technologies Diagnostic Tools > In Vitro Nanoparticle-Based Sensing Diagnostic Tools > In Vivo Nanodiagnostics and Imaging